Loss of stra8 Increases Germ Cell Apoptosis but Is Still Compatible With Sperm Production in Atlantic Salmon (Salmo salar) - Skaftnesmo, Kai O.; Crespo, Diego; Kleppe, Lene; Andersson, Eva; Edvardsen, Rolf B.; Norberg, Birgitta; Fjelldal, Per Gunnar; Hansen, Tom J.; Schulz, Rüdiger W.; Wargelius, Anna (Frontiers in Cell and Developmental Biology, 2021)
Entering meiosis strictly depends on stimulated by retinoic acid 8 (Stra8) gene function in mammals. This gene is missing in a number of fish species, including medaka and zebrafish, but is present in the majority of fishes, including Atlantic salmon. Here, we have examined the effects of removing stra8 on male fertility in Atlantic salmon. As in mammals, stra8 expression was restricted to germ cells in the testis, transcript levels increased during the start of puberty, and decreased when blocking the production of retinoic acid. We targeted the salmon stra8 gene with two gRNAs one of these were highly effective and produced numerous mutations in stra8, which led to a loss of wild-type (WT) stra8 expression in F0 salmon testis. In maturing stra8 crispants, the spermatogenetic tubuli were partially disorganized and displayed a 7-fold increase in germ cell apoptosis, in particular among type B spermatogonia and spermatocytes. The production of spermatogenic cysts, on the other hand, increased in maturing stra8 crispants. Gene expression analysis revealed unchanged (lin28a, ret) or reduced levels (egr1, dusp4) of transcripts associated with undifferentiated spermatogonia. Decreased expression was recorded for some genes expressed in differentiating spermatogonia including dmrt1 and ccnd2 or in spermatocytes, such as ccna1. Different from Stra8-deficient mammals, a large number of germ cells completed spermatogenesis, sperm was produced and fertilisation rates were similar in WT and crispant males. While loss of stra8 increased germ cell apoptosis during salmon spermatogenesis, crispants compensated this cell loss by an elevated production of spermatogenic cysts, and were able to produce functional sperm. It appears that also in a fish species with a stra8 gene in the genome, the critical relevance this gene has attained for mammalian spermatogenesis is not yet given, although detrimental effects of the loss of stra8 were clearly visible during maturation.